Respostas

A melhor resposta!
2014-04-19T19:42:07-03:00
Olá, FERNANDARIBEIRO1.

a) (A ∩ B) U H
(A ∩ B) = {3, 5}
{3, 5} ∩ H = {3, 4, 5, 6}

b) (A - B) U (B - A)
(A - B) = {4, 6}
(B - A) = {1, 7}
{4, 6} U {1, 7} = {1, 4, 6, 7}

c) (B U H) - A
(B U H) = {1, 3, 4, 5, 6, 7}
{1, 3, 4, 5, 6, 7} - A = {1, 7}
1 5 1
2014-04-19T19:42:46-03:00
A) { 3, 4, 5, 6}
b) {1, 4, 6, 7}
c) {1, 3, 4, 5, 6, 7}

Espero ter ajudado :)
1 5 1
ops a letra c eu errei, desculpe
Mesmo assim ajudou muito!!! Obrigada!!! :)
:) Que bom